A Solid State Transformer Based on a Three-Phase to Single-Phase Modular Multilevel Converter for Power Distribution Networks - Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2018)
To properly integrate electric vehicles and distributed generation systems in a massive scale, new revolutionary features and unprecedented transformations has to be implemented in power distribution networks, such as: access to LV DC interconnection point, reconfiguration capability for power flow management, disturbance isolation, low power-losses, high reliability, high power-quality, smart protection and low failure rate. In this paper, an innovative topology for a Solid State Transformer based on AC/AC Modular Multilevel Converter (MMC) is proposed. The proposed topology uses only one centralized single-phase Medium Frequency Transformer (MFT), which reduces the footprint of the SST. Furthermore, it provides three-phase balanced low-voltage system under unbalanced and non-linear loads. Simulation results validate the proposed topology and the control of the MMC to modulate a medium frequency medium-voltage to provide a desired power flow. © 2017 IEEE.